2012
DOI: 10.1186/1472-6750-12-23
|View full text |Cite
|
Sign up to set email alerts
|

Validation of glypican-3-specific scFv isolated from paired display/secretory yeast display library

Abstract: BackgroundGlypican-3 (GPC3) is a heparan-sulfate proteoglycan frequently expressed on the cell membrane of malignant hepatocytes in hepatocellular carcinoma. The capacity for screening potential antibodies in vitro using human hepatocellular lines is critical to ensure binding to this highly post-translationally modified glycophosphatidylinositiol-linked protein. We hypothesized that we could utilize a recently described paired display/secretory yeast library to isolate human-derived scFv against glypican-3 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…In conclusion, we, along with other investigators [39] , [75] have shown that affinity reagents raised against peptide fragments of membrane proteins are robust binders of the native receptor expressed both heterologously and in animal tissues. We have also shown that the K d values of these binders can be enhanced substantially by dimerization, which enables them to be useful tools in varied pharmacological and biochemical applications.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In conclusion, we, along with other investigators [39] , [75] have shown that affinity reagents raised against peptide fragments of membrane proteins are robust binders of the native receptor expressed both heterologously and in animal tissues. We have also shown that the K d values of these binders can be enhanced substantially by dimerization, which enables them to be useful tools in varied pharmacological and biochemical applications.…”
Section: Discussionsupporting
confidence: 66%
“…Traditionally, using membrane proteins as targets for selections has been problematic, in part due to the difficulty in expressing and purifying native protein that retains its structure and function [36] , [37] , [38] . However, scFvs against membrane proteins can be generated to peptide fragments of these proteins, thereby overcoming the need for generating purified protein targets [39] .…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on improved antibody applicability for immunotherapy have focused on the modification of conventional antibody molecules, such as single-chain antibodies, Fab antibodies, and Fv single domain antibodies. 33,34 However, these antibodies have many shortcomings such as cumbersome preparation processes, poor water solubility, and easy aggregation. Therefore, it is necessary to obtain more advantageous GPC3 antibodies to improve diagnostic sensitivity, targeting and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a novel scFv able to bind CD24, a target overexpressed by hepatocellular carcinoma (HCC), has been developed, showing a higher accumulation in the hepatocellular carcinoma xenograft mouse model and proving its potential as a therapeutic and diagnostic agent [128]. Another promising target expressed by malignant hepatocytes called Glypican-3 (GPC3) has already been exploited to isolate different scFvs with future potential applications [129,130].…”
Section: Scfv To Targetmentioning
confidence: 99%